Morphology and Molecular Phylogeny of the Soil Ciliate Cyrtohymena seorakensis sp. n. (Ciliophora, Hypotricha, Oxytrichidae) - Omar, Atef; Jung, Jae-Ho (Zootaxa, 2020)
The morphology and infraciliature of a new ciliate, Cyrtohymena seorakensis sp. n., discovered in a moss sample from South Korea, were investigated. The new species is distinguished from congeners by having rather fewer, randomly scattered, yellowish cortical granules, 23–30 adoral membranelles, invariably four transverse cirri in morphostatic specimens, and a total of 62 dorsal bristles on average. Phylogenetic analysis based on 18S rDNA sequences showed that the new species clusters with an Indian population of C. citrina.